Asymptomatic carriage of Plasmodium falciparum in children no longer targeted for seasonal malaria chemoprevention and with a history of exposure to this strategy: A cross sectional study in southern Senegal - Isaac Akhénaton Manga; Abdoulkarim Mhadji; Aminata Lam; Marie Pierre Diouf; Pab Carole Minlekib; Fassiatou Tairou; Amadou Seck; Babacar Faye; Magatte Ndiaye; Jean Louis Abdourahim Ndiaye (PLoS ONE, 2025)
Seasonal malaria chemoprevention (SMC) has been implemented in southern part of Senegal since 2013, targeting children 3–120 months old. This strategy is often evaluated among the population targeted for the intervention. This study was conducted to determine the prevalence of malaria in children who recently aged out of the target age range for SMC in Senegal. The study was conducted between September and December 2016 in Kédougou, Kolda and Sédhiou, located in southern Senegal where SMC is implemented. A questionnaire was administered to each participant to collect information on his history of SMC exposure and a blood sample collected on Whatman filter paper. The Pf18S gene was amplified by Real Time-PCR to detect Plasmodium falciparum. A total of 226 children between 11 and 14 years old were included in the study. The mean age was 11.9 (±0.8) years with a sex ratio (M/F) of 1.05. The overall malaria prevalence was 19.47%. Plasmodium falciparum parasite carriage was higher in children who had recently aged out of SMC eligibility (6.6% in 11-year-olds and 9.3% in 12-year-olds). In 2013, the prevalence was higher among children who had completed two cycles (5.3%). However, it was higher among those who had taken three cycles in 2014 (13.7%) and 2015 (5.8%). This study showed that the prevalence of P. falciparum was higher in children who had taken SMC in 2013 and 2014, with a prevalence of 6.6%. Children exposed in 2013, 2014 and 2015 had a prevalence of 2.65%. No parasite carriage was observed in children exposed in 2013, 2014, 2015 and 2016. Children protected by SMC become potential malaria parasites reservoirs when they leave the target age range. There is an urgent need of strategies, other than bed nets to continue protecting these populations.